Beyond the Guild: Lawyer Organizations and Law Making - Leslie C. Levin; Lynn Mather (Washington University Global Studies Law Review, 2019)
This Article examines when and why lawyer organizations seek to influence law, either by promoting change or opposing it. The Article compares the activities of lawyer organizations in specific countries, noting at times how they work in conjunction with international or regional lawyer organizations. It seeks to identify the factors that enable the organizations to act and the conditions that may prevent them from acting, focusing not on outcomes, but on attempts to affect law. These efforts include, for example, proposing, drafting or responding to rules or legislation, lobbying, filing lawsuits or amicus briefs, and engaging in strikes or other public protest. Examining the full range of lawyers’ efforts, we also include “pre-law making” activities such as problem definition, agenda setting, and mobilization for change, as well as implementation activities focused on enforcement or resistance. Because of governmental impediments to action by lawyer organizations in some jurisdictions, we also consider informal efforts by lawyers to engage in collective actions. Part I of this Article describes organizational theories and theories of the legal profession that might explain why lawyer organizations attempt to influence law. In Part II, the Article provides an overview of lawyers and their organizations in seven countries with very different political and legal systems. As an initial study of this issue, the small number of countries provides an opportunity to explore the question in some depth. Part II briefly describes the history of lawyers and their associations in these countries, their relationship to the courts and the state, and their view of their role in society. Part III then examines some situations in which lawyer organizations acted to influence law and other situations in which they stayed silent. Using examples from the seven countries, this Part identifies four somewhat overlapping categories in which lawyer organizations attempted to affect the law. Part IV revisits the theoretical perspectives to suggest when lawyer organizations will act, and when they will not. The Article concludes by identifying questions for further research.
Keywords: lawyer organization; lawyer union; lawyer association; bar association